Factors Related to Employment Outcomes for Vocational Rehabilitation Consumers with Visual Impairments: A Systematic Review. (November 2019) - Lund, Emily M.; Cmar, Jennifer L.
Introduction: The purpose of this article was to conduct a systematic review of peer-reviewed studies on factors related to employment in consumers who are visually impaired using Rehabilitation Services Administration (RSA-911) Case Service Report data. Methods: We used database, hand, and ancestral search strategies to systematically identify peer-reviewed studies published between 1990 and August 2018 where researchers used RSA-911 data to address the target question. All included articles were coded by two reviewers for study and participant characteristics, quality indicators, and outcomes. Results: Nine articles consisting of 14 analyses were included. Twelve analyses concerned employment outcomes; two concerned earnings. Researchers in most studies used large samples of 3, 000 or more consumers and used multivariable analyses, most commonly multilevel logistic regression. Factors that consistently predicted lower employment across studies included presence of a secondary disability and legal blindness; higher education level consistently predicted higher employment, as did earnings and self-support at vocational rehabilitation application. Few analyses included state- or agency-level variables or specific vocational rehabilitation services. Discussion: These results indicate that certain groups of vocational rehabilitation consumers with visual impairments may be at greater risk of unsuccessful closures; researchers should examine specific strategies that may improve outcomes in these groups. These results also highlight the importance of education in securing employment among people with visual impairments. Researchers should examine state- and agency-level variables that may affect outcomes as well as the effects of specific services on outcomes. Additionally, researchers should analyze factors that may affect employment quality as well as employment outcomes. Implications for practitioners: Practitioners who are working with visually impaired people who do not have a postsecondary degree should encourage and assist their clients in obtaining one; practitioners may also wish to provide more targeted support for consumers from potentially high-risk subpopulations.